tìm x
3 mũ x + 1 = 3 mũ 2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 75 : ( x - 18 ) = 52 = 25
=> x - 18 = 3
=> x = 21
b) 740 : ( x - 10 ) = 102 - 2 x 13
740 : ( x - 10 ) = 100 - 26 = 74
=> x - 10 = 10
=> x = 20
c) ( 2x - 5 )3 = 8 = 23
=> 2x - 5 = 2
=> 2x = 7
=> x= 7/2
d) ( 15 - 6x ) x 35 = 36
=> ( 15 - 6x ) = 36 : 35 = 3
=> 6x = 12
=> x = 2
a)152*32*53
=152*32*52*5
=152*(3*5)2*5
=152*152*5
=154*5
b)93*32*63*22
=(9*6)3*(3*2)2
=543*62
=(6*9)3*62
=63*93*62
=65*93
c)82*23
=82*8
=83
d)103*23*52
=(2*5)3*23*52
=23*53*23*52
=26*55
\(3^2.3^x.81-27^4=0\)
\(3^2.3^x.3^4-\left(3^3\right)^4=0\)
\(3^6.3^x-3^{12}=0\)
\(3^6.3^x-3^{12}=0\)
\(3^6.3^x=0+3^{12}\)
\(3^6.3^x=3^{12}\)
\(3^{6+x}=3^{12}\)
\(\Rightarrow6+x=12\)
\(x=12-6\)
\(\Rightarrow x=6\)
Bài 1
a) \(x=x^5\)
\(x^5-x=0\)
\(x\left(x^4-1\right)=0\)
\(x=0\) hoặc \(x^4-1=0\)
* \(x^4-1=0\)
\(x^4=1\)
\(x=1\)
Vậy x = 0; x = 1
b) \(x^4=x^2\)
\(x^4-x^2=0\)
\(x^2\left(x^2-1\right)=0\)
\(x^2=0\) hoặc \(x^2-1=0\)
*) \(x^2=0\)
\(x=0\)
*) \(x^2-1=0\)
\(x^2=1\)
\(x=1\)
Vậy \(x=0\); \(x=1\)
c) \(\left(x-1\right)^3=x-1\)
\(\left(x-1\right)^3-\left(x-1\right)=0\)
\(\left(x-1\right)\left[\left(x-1\right)^2-1\right]=0\)
\(x-1=0\) hoặc \(\left(x-1\right)^2-1=0\)
*) \(x-1=0\)
\(x=1\)
*) \(\left(x-1\right)^2-1=0\)
\(\left(x-1\right)^2=1\)
\(x-1=1\) hoặc \(x-1=-1\)
**) \(x-1=1\)
\(x=2\)
**) \(x-1=-1\)
\(x=0\)
Vậy \(x=0\); \(x=1\); \(x=2\)
Bài 1:
2\(x\) = 4
2\(^x\) = 22
\(x=2\)
Vậy \(x=2\)
Bài 2:
2\(^x\) = 8
2\(^x\) = 23
\(x=3\)
Vậy \(x=3\)
a) \(3^2.x+2^3.x=51\)
\(\Leftrightarrow x\left(3^2+2^3\right)=51\)
\(\Leftrightarrow17x=51\)
\(\Leftrightarrow x=3\)
Vậy
b) \(6^2.2-\left(84-3^2.x\right):7=69\)
\(\Leftrightarrow\left(84-3^2.x\right):7=3\)
\(\Leftrightarrow84-3^2.x=21\)
\(\Leftrightarrow3^2.x=63\)
\(\Leftrightarrow x=7\)
Vậy
3^x + 1 = 9
3^x = 9 - 1
3^x = 8
-> x thuộc rỗng
ĐÚNG CHO MK NHÉ!
3x+1 = 32
<=> x + 1 = 2
<=> x = 1